2021
DOI: 10.3389/fmars.2021.624322
|View full text |Cite
|
Sign up to set email alerts
|

Deoxygenation in Marginal Seas of the Indian Ocean

Abstract: This article describes oxygen distributions and recent deoxygenation trends in three marginal seas – Persian Gulf and Red Sea in the Northwestern Indian Ocean (NWIO) and Andaman Sea in the Northeastern Indian Ocean (NEIO). Vertically mixed water column in the shallow Persian Gulf is generally well-oxygenated, especially in winter. Biogeochemistry and ecosystems of Persian Gulf are being subjected to enormous anthropogenic stresses including large loading of nutrients and organic matter, enhancing oxygen demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 65 publications
(92 reference statements)
2
10
0
Order By: Relevance
“…In the same study, large-scale near-bottom hypoxia was observed both in summer and autumn with a total area estimated to potentially reach up to 50,000 km 2 in the autumn. These observations indicate a possible intensification of hypoxia in the deeper part of the Gulf as was also suggested by recent analyses of historical O 2 observations by Al-Yamani and Naqvi (2019) and Naqvi (2021).…”
Section: Introductionsupporting
confidence: 84%
“…In the same study, large-scale near-bottom hypoxia was observed both in summer and autumn with a total area estimated to potentially reach up to 50,000 km 2 in the autumn. These observations indicate a possible intensification of hypoxia in the deeper part of the Gulf as was also suggested by recent analyses of historical O 2 observations by Al-Yamani and Naqvi (2019) and Naqvi (2021).…”
Section: Introductionsupporting
confidence: 84%
“…A substantial portion of the Arabian Sea giant form population resides in deep and cool waters in the Northern Arabian Sea (200–350 m depth; 12–13°C temperature), which has a pronounced oxygen minimum layer (150 m). The stable mesopelagic oxygen minimum zone (OMZ) in the northwestern Indian Ocean (Naqvi 2021) is considered as a hot spot of organic matter re‐mineralization (Ragavan & Kumar 2021). This area is highly productive and is rich in lantern fishes, which form the major food item of the giant form.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that a change in DO consumption off central Chile is due to eutrophication in the Frontiers in Earth Science frontiersin.org 13 coastal system as rivers have a moderate or low N and P load (Masotti et al, 2018). This contrasts to the Gulf of Mexico or the continental shelf off India (Breitburg, et al, 2018;Naqvi, 2021), but it remains unclear if changes in water masses at mid latitudes, mainly the ESSW, are responsible for the observed deoxygenation.…”
Section: Long Term Variability: Decadal Trendsmentioning
confidence: 99%